Calcifying epithelioma of Malherbe – a rare localization - Iqbal, Banyameen; Putenparampil, Reshma A; Kambale, Tushar; Dharwadkar, Arpana; Viswanathan, Vidya (Polish Journal of Pathology, 2023)
Calcifying epithelioma of Malherbe, also known as pilomatricoma or pilomatrixoma, mostly arises in the matrix hair follicle. It generally affects the head and neck, upper extremities, and trunk, with the lower extremities being a rare exception. We hereby present a case of a 31-year-old male patient who presented with a small, firm, subcutaneous mass over the left malleolus, which was provisionally diagnosed as lipoma. Surgical excision was performed, and the histopathology report revealed it to be pilomatricoma of the left malleolus.